The Effect Of Counseling On The Management Of Food Ingredients (Moringa Leaves) Of Complementary Food On The Behavior Of Mothers Who Have Babies Aged 7-12 Months In Tegal Sari Village In 2022 - Herviza Wulandary Pane; Ustifina hasanah HSB (Science Midwifery, 2022)
Mother's behavior in providing complementary foods greatly affects the nutritional status of toddlers. One way to improve the behavior of mothers in providing complementary foods to breast milk is to provide health education. This study aims to determine the effect of counseling on the management of food ingredients (moringa leaves) MPASI on the behavior of mothers who have babies aged 7-12 months in Tegal Sari Village in 2022. The method used pre-experimental designwith pre-test and post-test group design. The sample with total sampling technique was 32 respondents. Data collection was carried out using a questionnaire. Data analysis using Wilcoxon testbecause the data were not normally distributed. The results showed that the behavior of mothers in providing complementary feeding to infants aged 6-12 months after receiving counseling on the management of food ingredients (moringa leaves) was mostly good, as many as 19 people (59.4%). The results of statistical test analysis showed that there was a significant difference with the value of z=-5.109 (p<0.05). This shows that there is a significant influence on the behavior of mothers in providing complementary foods to breast milk before and after health education is carried out on the management of food ingredients (moringa leaves).